Radar-infrared multi-spectrum compatible stealth composite material and preparation method thereof
By using a double-layer structure and laser etching cycle pattern in radar-infrared multi-spectrum compatible stealth composite materials, the problem of difficulty in achieving radar and infrared stealth effects simultaneously in the prior art is solved, and a more efficient multi-spectrum stealth effect is achieved.
Patent Information
- Application Number
- CN202510201697.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-24
AI Technical Summary
The prior art is difficult to achieve strong absorption in the radar band and low emission in the infrared band at the same time, resulting in poor multi-spectrum stealth effect.
The radar-infrared multi-spectrum compatible stealth composite material with a double-layer structure, the upper layer is an infrared shielding reflective layer with a periodic pattern of laser etching, and the lower layer is a wave absorbing heat insulation layer. By redesigning the shape of the periodic unit and adjusting the periodic unit size and laser etching gap, the radar wave transmittance and reduce the infrared emissivity.
It achieves the reduction of infrared transmittance while increasing the radar wave transmittance, improving the multi-spectral stealth effect of the material.
Smart Images

Figure CN119682328A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of stealth materials and relates to a radar-infrared multi-spectrum compatible stealth composite material and a preparation method thereof. Background Art
[0002] With the rapid development of military reconnaissance technology, surveillance equipment is increasingly used. Among them, multi-spectrum complementary stealth technology, especially radar and infrared compatible stealth technology, has attracted much attention because it can effectively cope with complex and changeable detection systems. Radar stealth technology requires materials to have excellent electromagnetic wave attenuation capabilities, that is, high absorption and low reflection; while infrared stealth technology requires materials to have high reflection and low emission characteristics. However, there is an obvious contradiction between the requirements of these two stealth technologies on material absorption rate, which brings severe challenges to the development of stealth materials that have the advantages of both.
[0003] Specifically, radar stealth performance is usually measured by radar wave transmittance. An ideal material should have a higher radar wave transmittance so as to better absorb incident electromagnetic waves. Infrared stealth performance is evaluated by infrared emissivity. In the two key bands of 3-5μm and 8-14μm, the lower the infrared emissivity, the weaker the infrared radiation of the material. Usually, a value less than 0.3 is used as an excellent evaluation indicator.
[0004] In order to meet the requirements of both radar and infrared stealth, researchers usually try to design composite materials or layered structures. These designs aim to achieve strong absorption in the radar band and low emission in the infrared band. However, despite many efforts, achieving good multi-spectrum stealth effects still faces many difficulties.
[0005] As an advanced solution, metamaterials have shown significant advantages in multi-physics stealth technology. The core concept is to use the difference between radar and infrared wavelengths to manipulate electromagnetic waves by building a layered structure. In this design, the top layer of infrared stealth usually adopts a frequency domain selective surface (i.e., a low-pass filter), which allows radar waves to pass through while maintaining a low emissivity of the overall structure. The metamaterial absorber at the bottom is responsible for attenuating and absorbing radar waves transmitted from the top layer. However, metamaterials still face many challenges in practical applications, including complex processing, high cost, poor thermal insulation performance, and the need for a large thickness to achieve broadband response. These problems limit the further development and widespread application of metamaterials.
[0006] In view of the potential of metamaterials in multi-physics field stealth technology and the challenges it faces, the literature (Asymmetricelectric field distribution enhanced hierarchical metamaterials for radar-infrared compatible camouflage[J]. Journal of Materials Science & Technology, 2023, 146: 10-18.) uses carbonyl iron particles, graphene sheets and polyurethane to prepare a wave-absorbing and heat-insulating layer, uses laser-etched square patterns to prepare an infrared shielding and reflecting layer, and then uses polyurethane glue to stick the infrared shielding and reflecting layer on top of the wave-absorbing and heat-insulating layer to prepare a double-layer compatible stealth material. However, the radar wave transmittance of this material needs to be further improved, and the infrared emissivity needs to be further reduced. Summary of the invention
[0007] The purpose of the present invention is to solve the problems existing in the prior art and to provide a radar-infrared multi-spectrum compatible stealth composite material and a preparation method thereof.
[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] A radar-infrared multi-spectrum compatible stealth composite material, having a double-layer structure, wherein the upper layer is an infrared shielding and reflecting layer having a laser-etched periodic pattern, and the lower layer is a wave-absorbing and heat-insulating layer, wherein the periodic unit of the periodic pattern (a basic unit that can appear repeatedly in a periodic structure and constitute the entire structure) is in the shape of a cross rectangle, a diamond, a bagua, a cross circle, a circle or a cross rectangle;
[0010] The cross-shaped rectangle is composed of a rectangle and eight line segments inside it. One end of the eight line segments is connected to the center point of the rectangle at the same time, and the other ends are connected to the four vertices of the rectangle and the midpoints of the four sides of the rectangle respectively.
[0011] The cross circle is composed of a circle and four line segments inside it. One end of the four line segments is connected to the center of the circle at the same time, and the other end is connected to four points evenly distributed on the circle.
[0012] The cross rectangle consists of a rectangle and four line segments inside it. One end of the four line segments is connected to the center point of the rectangle at the same time, and the other end is connected to the four vertices of the rectangle respectively.
[0013] The periodic unit size is 0.5-1.0 mm, and the laser etching gap is 35-60 μm.
[0014] When the laser etching gap and the shape of the periodic unit remain unchanged, after reducing the size of the periodic unit, the area ratio of the conductive part will decrease, and the radar wave transmittance will increase, but the infrared emissivity, which is inversely proportional to the area ratio of the conductive part, will also increase. Therefore, it is difficult to further increase the radar wave transmittance and further reduce the infrared emissivity by simply reducing the size of the periodic unit. The present invention achieves further reducing the infrared emissivity while further increasing the radar wave transmittance by redesigning the shape of the periodic unit and coordinating with the size of the periodic unit and the laser etching gap.
[0015] As the preferred technical solution:
[0016] As described above, a radar-infrared multi-spectrum compatible stealth composite material, the infrared shielding reflective layer includes an infrared shielding material located at the upper layer and a substrate located at the lower layer, the thickness of the infrared shielding material is 0.03-0.1mm, and the thickness of the substrate is 0.1-0.2mm; the infrared shielding material is aluminum foil, copper foil, silver foil, indium tin oxide film or conductive spray paint, and the substrate is a polycarbonate plate.
[0017] In the radar-infrared multi-spectrum compatible stealth composite material as described above, the thickness of the absorbing and heat-insulating layer is 2.5-3.5 mm; the absorbing and heat-insulating layer is aerogel, the skeleton of the aerogel is aramid nanofiber, and the aramid nanofiber is obtained by deprotonating and protonating short-cut Kevlar fibers in a solvent (dimethyl sulfoxide) in sequence.
[0018] As described above, a radar-infrared multi-spectrum compatible stealth composite material, aramid nanofibers are attached with MXene, the MXene sheet diameter is 1-20μm, MXene is a two-dimensional material, and the rich functional groups and lattice defects on MXene and the excellent electrical conductivity provide a free electron transmission path for electromagnetic wave attenuation, effectively converting electromagnetic waves into heat energy.
[0019] In the radar-infrared multi-spectrum compatible stealth composite material as described above, Fe3O4@CPPy is also attached to the aramid nanofiber. Fe3O4@CPPy is a chiral nanoparticle with a core-shell structure, wherein the core is Fe3O4 nanoparticles and the shell is chiral polypyrrole with an average particle size of 340-400nm. Fe3O4@CPPy is a zero-dimensional material. Compared with ordinary zero-dimensional materials, it has interface polarization and dipole polarization, which can further improve the attenuation capability of radar waves.
[0020] As described above, the preparation process of the radar-infrared multi-spectrum compatible stealth composite material, Fe3O4@CPPy, is as follows: after Fe3O4 nanoparticles are prepared by a hydrothermal method, they are added together with pyrrole monomers into a system containing a chiral dopant or a chiral acid for polymerization to obtain Fe3O4@CPPy.
[0021] The preparation process of the radar-infrared multi-spectrum compatible stealth composite material Fe3O4@CPPy is as follows: FeCl3-6H2O, polyethylene glycol, and anhydrous sodium acetate are dissolved in ethylene glycol, reacted at 180-220°C for 8-10h, the reactant is washed to obtain Fe3O4 nanoparticles, and the Fe3O4 nanoparticles and pyrrole monomer are added to L-H2O at a concentration of 0.5-1.5 mol / L. - Ammonium persulfate solution was added dropwise to the camphorsulfonic acid solution, polymerized in an ice-water bath for 2-4 h, and the precipitate was washed to obtain Fe3O4@CPPy.
[0022] In the radar-infrared multi-spectrum compatible stealth composite material as described above, the content of MXene in the aerogel is 20-30wt%, and the content of Fe3O4@CPPy is 10-30wt%. The aerogel has an infrared stealth effect. Because the porous structure of the aerogel gives it thermal insulation performance, the upper surface temperature is much lower than the lower surface temperature contacting the heat source, so the radiated infrared signal is suppressed. The evaluation index of thermal insulation performance is mainly thermal conductivity. The aerogel of the present invention has a small thermal conductivity and excellent thermal insulation performance, which is beneficial to improving the infrared stealth effect of the composite material.
[0023] A radar-infrared multi-spectrum compatible stealth composite material as described above, the radar-infrared multi-spectrum compatible stealth composite material has an absorption bandwidth of 8.4-12.4 GHz in the X-band (8.2-12.4 GHz, a specific frequency band in the radar band), a minimum reflection loss of -32.44~-14.4 dB, a thermal conductivity of 0.0274-0.0320 W / (m·K) (the thermal conductivity of the radar-infrared multi-spectrum compatible stealth composite material is that of the absorbing and heat-insulating layer), an average infrared emissivity of 0.18-0.28 in the 3-5 μm infrared band, an average infrared emissivity of 0.15-0.26 in the 8-14 μm infrared band, and a surface temperature of 46.6-58.6°C after continuous heating on a 150°C heating table for 0.5 h.
[0024] The present invention also provides a method for preparing a radar-infrared multi-spectrum compatible stealth composite material as described in any of the above items, after separately preparing an infrared shielding reflection layer and a wave-absorbing heat-insulating layer with a laser-etched periodic pattern, the two are assembled together by glue to obtain a radar-infrared multi-spectrum compatible stealth composite material.
[0025] Beneficial effects:
[0026] (1) The present invention achieves the goal of further improving radar wave transmittance while further reducing infrared emissivity by redesigning the shape of the periodic unit and coordinating the periodic unit size and laser etching gap.
[0027] (2) The present invention uses aerogel as the wave-absorbing and heat-insulating layer of the radar-infrared multi-spectrum compatible stealth composite material. Due to its unique structure and extremely low density, aerogel has a low thermal conductivity, which can effectively prevent the transfer of heat from bottom to top and significantly reduce the upper surface temperature of the material, thereby suppressing the radiation of infrared signals and improving the infrared stealth effect of the composite material.
[0028] (3) The aerogel used in the present invention has the characteristics of increasing the transmission path length of electromagnetic waves inside the material, enhancing the attenuation effect of microwaves and promoting effective scattering, and improving the absorption and conversion capabilities of electromagnetic waves due to its high specific surface area, rich porous structure, heterogeneous structure and electron transmission ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic diagram of the overall structure of the radar-infrared multi-spectrum compatible stealth composite material of Example 1;
[0030] Figure 2 Schematic diagram of periodic unit size and laser etching gap of different periodic patterns; wherein w represents the periodic unit size, p represents the laser etching gap, EMW represents electromagnetic wave, dc represents the thickness of infrared shielding material, and dt represents the thickness of substrate;
[0031] Figure 3 The SEM diagram of the periodic pattern etched by laser on the infrared shielding material; wherein (a) corresponds to Example 1, (b) corresponds to Example 3, (c) corresponds to Example 4, and (d) corresponds to Example 5;
[0032] Figure 4 The middle one is the TEM image of Fe3O4@CPPy of Example 1 (only one particle is selected as an example);
[0033] Figure 5 (a) is a reflection loss curve obtained by testing the radar-infrared multi-spectrum compatible stealth composite material of Example 1, Figure 5 (b) is a diagram showing the transmittance and reflectance of the infrared shielding reflection layer of Example 1 to radar waves;
[0034] Figure 6 is the infrared reflectivity obtained by testing the radar-infrared multi-spectrum compatible stealth composite material of Example 1;
[0035] Figure 7 (a) is the SEM image of Fe3O4 in Example 2. Figure 7 (b) is a reflection loss curve obtained by testing the radar-infrared multi-spectrum compatible stealth composite material of Example 2;
[0036] Figure 8(a) is a reflection loss curve obtained by testing the radar-infrared multi-spectrum compatible stealth composite material of Example 3, Figure 8 (b) is a diagram showing the transmittance and reflectance of the infrared shielding reflection layer of Example 3 to radar waves;
[0037] Fig. 9 (a) is a reflection loss curve obtained by testing the radar-infrared multi-spectrum compatible stealth composite material of Example 4, Fig. 9 (b) is a graph showing the transmittance and reflectance of the infrared shielding reflection layer of Example 4 to radar waves. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0039] The following are the test methods for the relevant performance indicators in each embodiment:
[0040] Thermal conductivity: measured using TPA-2500S thermal constant analyzer in accordance with standard ISO-22007-2 transient plane heat source method.
[0041] The absorption performance (absorption bandwidth, reflection loss) of radar-infrared multi-spectrum compatible stealth composite materials in the X-band, and the transmittance and reflectivity of the infrared shielding reflective layer to radar waves require mathematical calculation and software simulation of the electromagnetic parameters (complex magnetic permeability, complex dielectric constant) of the radar-infrared multi-spectrum compatible stealth composite materials themselves; the electromagnetic parameters are obtained using a Keysight E5080B model vector network analyzer in accordance with GB / T 35679-2017, with a frequency setting range of 8.2-12.4GHz and a sample size of 22.85mm×10.15mm;
[0042] The calculation formula of reflection loss RL (dB) is as follows:
[0043] ;
[0044] ;
[0045] In the formula, is the input impedance (Ω), is the impedance of air (377Ω), is the thickness of the radar-infrared multi-spectrum compatible stealth composite material (mm), is the frequency (GHz), is the complex magnetic permeability obtained by the test, is the complex dielectric constant obtained by the test, is the speed of light (3×10 8 m / s);
[0046] The absorption bandwidth of radar-infrared multi-spectrum compatible stealth composite materials in the X-band is calculated as In the frequency range of ≤-10dB, the minimum reflection loss is calculated. Minimum value;
[0047] The transmittance and reflectivity of the infrared shielding reflection layer to radar waves are simulated by CST Studio software. The modeling of the infrared shielding reflection layer is completed using the software's own commands. The electromagnetic parameters of the infrared shielding material and substrate select the default data in the software material library. The simulation setting conditions are that the direction of the incident electromagnetic field is opposite to the Z axis, the pattern model is located in the XOY plane, the frequency domain solver and open boundary are selected, and the tetrahedral mesh is divided. The transmittance is the simulated data SZmin(1), Zmax(1), and the reflectivity is SZmax(1), Zmax(1) data.
[0048] Average infrared emissivity in the 3-5μm infrared band: Use Nicolet 6700 Fourier infrared spectrometer (including integrating sphere accessory) to measure the infrared reflectivity and infrared absorptivity of the sample in the 3-5μm infrared band in accordance with GB / T 21186-2007 standard. Calculate the infrared emissivity of the sample in the 3-5μm infrared band based on Kirchhoff's law (infrared emissivity = 1-infrared reflectivity-infrared absorptivity). After processing, the average infrared emissivity of the sample in the 3-5μm infrared band is obtained.
[0049] Average infrared emissivity in the 8-14μm infrared band: Use Nicolet 6700 Fourier infrared spectrometer (including integrating sphere accessory) to measure the infrared reflectivity and infrared absorptivity of the sample in the 8-14μm infrared band in accordance with GB / T 21186-2007 standard. Calculate the infrared emissivity of the sample in the 8-14μm infrared band based on Kirchhoff's law (infrared emissivity = 1-infrared reflectivity-infrared absorptivity). After processing, the average infrared emissivity of the sample in the 8-14μm infrared band is obtained.
[0050] Infrared stealth performance: Use a T1050sc infrared thermal imaging camera to continuously detect the infrared imaging of the sample to be tested, and record its surface temperature after heating on a 150℃ heating table for 0.5h.
[0051] In the following embodiments, when the periodic unit shape of the laser-etched periodic pattern on the infrared shielding reflective layer is a square, the periodic unit size of the periodic pattern and the laser-etched gap are as follows: Figure 2 As shown in (a); when the periodic unit shape of the laser-etched periodic pattern on the infrared shielding reflective layer is a cross square, the periodic unit size of the periodic pattern and the laser-etched gap are as follows Figure 2 As shown in (b); when the periodic unit shape of the laser-etched periodic pattern on the infrared shielding reflective layer is a rhombus, the periodic unit size of the periodic pattern and the laser-etched gap are as follows Figure 2 As shown in (c), the minimum internal angle of the rhombus is 60°; when the periodic unit shape of the laser-etched periodic pattern on the infrared shielding reflective layer is a cross rectangle, the periodic unit size of the periodic pattern and the laser etching gap are as follows: Figure 2 As shown in (d), the length of the rectangle is When the periodic unit shape of the laser-etched periodic pattern on the infrared shielding reflective layer is circular, the periodic unit size of the periodic pattern and the laser-etched gap are as follows: Figure 2 As shown in (e); when the periodic unit shape of the laser-etched periodic pattern on the infrared shielding reflective layer is a cross circle, the periodic unit size of the periodic pattern and the laser etching gap are as follows Figure 2 As shown in (f); when the periodic unit shape of the laser-etched periodic pattern on the infrared shielding reflective layer is a Bagua shape, the periodic unit size of the periodic pattern and the laser etching gap are as follows Figure 2 As shown in (g).
[0052] In the following embodiments, the preparation process of the homogeneous dispersion of aramid nanofibers is as follows: chopped Kevlar fibers (manufacturer: DuPont, brand: 1414), potassium hydroxide, dimethyl sulfoxide, and deionized water are mixed, stirred at a temperature of 20°C and a rotation speed of 1000 r / min for 6 hours, deionized water is added again, stirred at a temperature of 20°C and a rotation speed of 600 r / min for 4 hours, and a homogeneous dispersion of aramid nanofibers is obtained by repeated suction filtration and washing; wherein the mass ratio of chopped Kevlar fibers to potassium hydroxide is 1:1.5, the mass ratio of chopped Kevlar fibers to dimethyl sulfoxide is 1:250, the mass ratio of dimethyl sulfoxide to the deionized water added for the first time is 25:1, and the volume ratio of the deionized water added for the second time to the deionized water added for the first time is 150:1.
[0053] Example 1
[0054] A method for preparing a radar-infrared multi-spectrum compatible stealth composite material, the specific steps are as follows:
[0055] (1) Preparation of raw materials;
[0056] FeCl3-6H2O: CAS number is 10025-77-1;
[0057] Polyethylene glycol: CAS number is 25322-68-3;
[0058] Anhydrous sodium acetate: CAS number is 127-09-3;
[0059] Ethylene glycol: CAS number is 107-21-1;
[0060] Pyrrole monomer: CAS number is 109-97-7;
[0061] L - Camphorsulfonic acid solution: concentration is 1 mol / L, the solvent is deionized water;
[0062] Ammonium persulfate solution: concentration is 1 mol / L, the solvent is deionized water;
[0063] Infrared shielding material: aluminum foil, thickness 0.05mm;
[0064] Substrate: polycarbonate sheet, manufactured by Dongguan Hongyan Plastic Co., Ltd., thickness 0.15mm;
[0065] A homogenous dispersion of aramid nanofibers;
[0066] MXene: The manufacturer is Jiangsu Xianfeng Nanomaterials Co., Ltd., and the flake diameter is 1-20 μm;
[0067] Glue: The manufacturer is Shenzhen Yishangxiang Electronic Materials Co., Ltd., brand name is YS1996;
[0068] (2) Preparation of Fe3O4@CPPy;
[0069] FeCl3-6H2O, polyethylene glycol, and anhydrous sodium acetate were dissolved in ethylene glycol and reacted at 200°C for 8 h. After washing the reactants to obtain Fe3O4 nanoparticles, Fe3O4 nanoparticles and pyrrole monomers were added to L - Ammonium persulfate solution was added dropwise to the camphorsulfonic acid solution, and the mixture was polymerized in an ice-water bath for 4 h. The precipitate was washed to obtain Fe3O4@CPPy with an average particle size of 360 nm. The mass ratio of FeCl3-6H2O, polyethylene glycol and anhydrous sodium acetate was 1.3:1:3.6, the mass ratio of ethylene glycol to the total mass of FeCl3-6H2O, polyethylene glycol and anhydrous sodium acetate was 10:1, and the Fe3O4 nanoparticles, pyrrole monomers, and L - The mass ratio of camphorsulfonic acid solution to ammonium persulfate solution is 2:1:500:200;
[0070] The TEM images of Fe3O4@CPPy are shown in Figure 2. Figure 4 As shown, from Figure 4 It can be seen that Fe3O4@CPPy has a core-shell structure, in which the core is Fe3O4 nanoparticles and the shell is chiral polypyrrole (see the dotted area);
[0071] (3) preparing an infrared shielding reflective layer and an aerogel respectively;
[0072] The preparation process of the infrared shielding reflective layer is as follows: the infrared shielding material is attached to the substrate by glue, and the surface of the infrared shielding material is etched by a laser marking machine at a laser etching speed of 200 mm / s and an etching power of 80%, so as to obtain an infrared shielding reflective layer with a laser-etched periodic pattern; the periodic unit shape of the periodic pattern is a square (SEM as shown in FIG. Figure 3 As shown in (a), the cross-shaped square consists of a square and 8 line segments inside it. One end of the 8 line segments is connected to the center point of the square at the same time, and the other end is connected to the 4 vertices of the square and the midpoints of the 4 sides of the square respectively. The periodic unit size is 1mm, and the laser etching gap is 35μm.
[0073] The preparation process of aerogel is as follows: the homogeneous dispersion of aramid nanofibers, MXene and Fe3O4@CPPy are mixed evenly, put into a mold, frozen in liquid nitrogen at -80°C for 12 hours, and then dried at -50°C to remove the solvent to obtain aerogel; the thickness of the aerogel is 2.9mm; the content of MXene in the aerogel is 25wt%, and the content of Fe3O4@CPPy is 10wt%;
[0074] (4) Preparation of radar-infrared multi-spectrum compatible stealth composite materials;
[0075] The infrared shielding reflective layer and the aerogel are assembled with glue to obtain a radar-infrared multi-spectrum compatible stealth composite material.
[0076] like Figure 1 As shown, the radar-infrared multi-spectrum compatible stealth composite material finally prepared is composed of an upper infrared shielding reflective layer and a lower aerogel, and the infrared shielding reflective layer is composed of an upper infrared shielding material and a lower substrate, and the upper infrared shielding reflective layer can reflect infrared waves and allow electromagnetic waves to pass through, while the lower aerogel can absorb electromagnetic waves that may pass through and effectively block the heat transmitted from below;
[0077] The radar-infrared multi-spectrum compatible stealth composite material has an absorption bandwidth of 8.7-12.4GHz in the X-band, and a minimum reflection loss of -32.44dB (the reflection loss curve is shown in Figure 5 As shown in (a), the transmittance and reflectivity of the infrared shielding reflection layer to radar waves are as follows Figure 5As shown in (b); the thermal conductivity of the radar-infrared multi-spectrum compatible stealth composite material is 0.0288W / (m·K); the average infrared emissivity of the radar-infrared multi-spectrum compatible stealth composite material in the 3-5μm infrared band is 0.23, and the average infrared emissivity in the 8-14μm infrared band is 0.25 (the infrared reflectivity curve is shown in Figure 6 As shown in the figure), the surface temperature was 50.2℃ after continuous heating on a 150℃ heating table for 0.5h.
[0078] Comparative Example 1
[0079] A method for preparing a composite material, which is different from Example 1 only in that the periodic unit shape of the periodic pattern is a square, and the size of the square is the same as the size of the square constituting the cross-shaped square in Example 1.
[0080] In the final composite material, the maximum transmittance of the infrared shielding reflection layer to radar waves is 74.82%, and the minimum is 56.25%.
[0081] Compared with Example 1, while keeping the periodic size and the laser etching gap unchanged, the maximum and minimum transmittance of the infrared shielding reflective layer to radar waves in the composite material are significantly reduced. This is because the periodic unit shape used in Comparative Example 1 is square. When the periodic unit size is 1 mm, the conductive part area accounts for a larger proportion, and the coupling with the radar wave is stronger, resulting in more reflections and reduced transmittance.
[0082] Example 2
[0083] A method for preparing a radar-infrared multi-spectrum compatible stealth composite material, which differs from Example 1 only in that: Fe3O4 nanoparticles are prepared in step (2). The specific preparation process is: FeCl3-6H2O, polyethylene glycol, and anhydrous sodium acetate are dissolved in ethylene glycol, reacted at 200°C for 8h, and the reactant is washed to obtain Fe3O4 nanoparticles (SEM as shown in FIG. Figure 7 As shown in (a)); in step (3), when preparing the aerogel, Fe3O4@CPPy is replaced with Fe3O4 nanoparticles of equal mass.
[0084] The radar-infrared multi-spectrum compatible stealth composite material finally obtained has an absorption bandwidth of 10.5-12.4GHz in the X-band and a minimum reflection loss of -14.4dB (the reflection loss curve is shown in Figure 7The thermal conductivity of the radar-infrared multi-spectrum compatible stealth composite material is 0.0274W / (m·K); the average infrared emissivity of the radar-infrared multi-spectrum compatible stealth composite material in the 3-5μm infrared band is 0.24, and the average infrared emissivity in the 8-14μm infrared band is 0.25. After continuous heating on a 150℃ heating table for 0.5h, the surface temperature is 48.8℃.
[0085] By comparing Example 2 with Example 1, it can be seen that compared with the Fe3O4 nanoparticles used in Example 2, the Fe3O4@CPPy used in Example 1 can improve the impedance matching of the material, increase the conductivity loss, provide various relaxation losses such as interface polarization and dipole polarization, achieve attenuation and absorption of radar waves, and enhance the radar stealth effect.
[0086] Example 3
[0087] A method for preparing a radar-infrared multi-spectrum compatible stealth composite material, which differs from Example 1 only in that the periodic unit shape of the laser-etched periodic pattern on the infrared shielding reflection layer is a rhombus (SEM as shown in FIG. Figure 3 As shown in (b), the periodic unit size is 0.55 mm and the laser etching gap is 35 μm.
[0088] The radar-infrared multi-spectrum compatible stealth composite material finally obtained has an absorption bandwidth of 9.2-12.4GHz in the X-band and a minimum reflection loss of -32.2dB (the reflection loss curve is shown in Figure 8 As shown in (a), the transmittance and reflectivity of the infrared shielding reflection layer to radar waves are as follows Figure 8 As shown in (b); the thermal conductivity of the radar-infrared multi-spectrum compatible stealth composite material is 0.0286W / (m·K); the average infrared emissivity of the radar-infrared multi-spectrum compatible stealth composite material in the 3-5μm infrared band is 0.18, and the average infrared emissivity in the 8-14μm infrared band is 0.15. After continuous heating on a 150℃ heating table for 0.5h, the surface temperature is 46.6℃.
[0089] Example 4
[0090] A method for preparing a radar-infrared multi-spectrum compatible stealth composite material, the specific steps are as follows:
[0091] (1) Preparation of raw materials;
[0092] FeCl3-6H2O: CAS number is 10025-77-1;
[0093] Polyethylene glycol: CAS number is 25322-68-3;
[0094] Anhydrous sodium acetate: CAS number is 127-09-3;
[0095] Ethylene glycol: CAS number is 107-21-1;
[0096] Pyrrole monomer: CAS number is 109-97-7;
[0097] L - Camphorsulfonic acid solution: concentration is 1.5 mol / L, the solvent is deionized water;
[0098] Ammonium persulfate solution: concentration is 1 mol / L, the solvent is deionized water;
[0099] Infrared shielding material: silver foil, thickness 0.03mm;
[0100] Substrate: polycarbonate sheet, manufactured by Dongguan Hongyan Plastic Co., Ltd., thickness 0.15mm;
[0101] A homogenous dispersion of aramid nanofibers;
[0102] MXene: The manufacturer is Jiangsu Xianfeng Nanomaterials Co., Ltd., and the flake diameter is 1-20 μm;
[0103] Glue: The manufacturer is Shenzhen Yishangxiang Electronic Materials Co., Ltd., brand name is YS1996;
[0104] (2) Preparation of Fe3O4@CPPy;
[0105] FeCl3-6H2O, polyethylene glycol, and anhydrous sodium acetate were dissolved in ethylene glycol and reacted at 180°C for 10 h. After washing the reactants to obtain Fe3O4 nanoparticles, Fe3O4 nanoparticles and pyrrole monomers were added to L - Ammonium persulfate solution was added dropwise to the camphorsulfonic acid solution, and the polymerization was carried out in an ice-water bath for 4 h. The precipitate was washed to obtain Fe3O4@CPPy with an average particle size of 400 nm; wherein the mass ratio of FeCl3-6H2O, polyethylene glycol and anhydrous sodium acetate was 1.2:1:4, the mass ratio of ethylene glycol to the total mass of FeCl3-6H2O, polyethylene glycol and anhydrous sodium acetate was 8:1, and the Fe3O4 nanoparticles, pyrrole monomers, and L - The mass ratio of camphorsulfonic acid solution to ammonium persulfate solution is 2:1.2:500:200;
[0106] (3) preparing an infrared shielding reflective layer and an aerogel respectively;
[0107] The preparation process of the infrared shielding reflective layer is as follows: the infrared shielding material is attached to the substrate by glue, and the surface of the infrared shielding material is etched by a laser marking machine at a laser etching speed of 220 mm / s and an etching power of 70%, so as to obtain an infrared shielding reflective layer with a laser-etched periodic pattern; the periodic unit shape of the periodic pattern is a cross circle (SEM as shown in FIG. Figure 3 As shown in (c), the cross circle consists of a circle and four line segments inside it. One end of the four line segments is connected to the center of the circle at the same time, and the other end is connected to four points evenly distributed on the circle. The periodic unit size is 0.9 mm, and the laser etching gap is 35 μm.
[0108] The preparation process of aerogel is as follows: the homogeneous dispersion of aramid nanofibers, MXene and Fe3O4@CPPy are mixed evenly, put into a mold, frozen in liquid nitrogen at -80°C for 12 hours, and then dried at -50°C to remove the solvent to obtain aerogel; the thickness of the aerogel is 3.1mm; the content of MXene in the aerogel is 30wt%, and the content of Fe3O4@CPPy is 15wt%;
[0109] (4) Preparation of radar-infrared multi-spectrum compatible stealth composite materials;
[0110] The infrared shielding reflective layer and the aerogel are assembled with glue to obtain a radar-infrared multi-spectrum compatible stealth composite material.
[0111] The radar-infrared multi-spectrum compatible stealth composite material finally prepared is composed of an upper infrared shielding reflection layer and a lower aerogel layer, and the infrared shielding reflection layer is composed of an upper infrared shielding material and a lower substrate;
[0112] The radar-infrared multi-spectrum compatible stealth composite material has an absorption bandwidth of 8.4-12.3GHz in the X-band, and a minimum reflection loss of -18.2dB (the reflection loss curve is shown in Fig. 9 As shown in (a), the transmittance and reflectivity of the infrared shielding reflection layer to radar waves are as follows Fig. 9 As shown in (b); the thermal conductivity of the radar-infrared multi-spectrum compatible stealth composite material is 0.0308W / (m·K); the average infrared emissivity of the radar-infrared multi-spectrum compatible stealth composite material in the 3-5μm infrared band is 0.23, and the average infrared emissivity in the 8-14μm infrared band is 0.20. After continuous heating on a 150℃ heating table for 0.5h, the surface temperature is 51.4℃.
[0113] Example 5
[0114] A method for preparing a radar-infrared multi-spectrum compatible stealth composite material, the specific steps are as follows:
[0115] (1) Preparation of raw materials;
[0116] FeCl3-6H2O: CAS number is 10025-77-1;
[0117] Polyethylene glycol: CAS number is 25322-68-3;
[0118] Anhydrous sodium acetate: CAS number is 127-09-3;
[0119] Ethylene glycol: CAS number is 107-21-1;
[0120] Pyrrole monomer: CAS number is 109-97-7;
[0121] L - Camphorsulfonic acid solution: concentration is 1.0 mol / L, the solvent is deionized water;
[0122] Ammonium persulfate solution: concentration is 0.5 mol / L, the solvent is deionized water;
[0123] Infrared shielding material: indium tin oxide film, thickness 0.1mm;
[0124] Substrate: polycarbonate sheet, manufactured by Dongguan Hongyan Plastic Co., Ltd., thickness 0.15mm;
[0125] A homogenous dispersion of aramid nanofibers;
[0126] MXene: The manufacturer is Jiangsu Xianfeng Nanomaterials Co., Ltd., and the flake diameter is 1-20 μm;
[0127] Glue: The manufacturer is Shenzhen Yishangxiang Electronic Materials Co., Ltd., brand name is YS1996;
[0128] (2) Preparation of Fe3O4@CPPy;
[0129] FeCl3-6H2O, polyethylene glycol, and anhydrous sodium acetate were dissolved in ethylene glycol and reacted at 190°C for 9 h. After washing the reactants to obtain Fe3O4 nanoparticles, Fe3O4 nanoparticles and pyrrole monomers were added to L - Ammonium persulfate solution was added dropwise to the camphorsulfonic acid solution, and the mixture was polymerized in an ice-water bath for 2 h. The precipitate was washed to obtain Fe3O4@CPPy with an average particle size of 340 nm. The mass ratio of FeCl3-6H2O, polyethylene glycol and anhydrous sodium acetate was 1.5:1:3, the mass ratio of ethylene glycol to the total mass of FeCl3-6H2O, polyethylene glycol and anhydrous sodium acetate was 12:1, and the Fe3O4 nanoparticles, pyrrole monomers, and L - The mass ratio of camphorsulfonic acid solution to ammonium persulfate solution is 2:1:500:150;
[0130] (3) preparing an infrared shielding reflective layer and an aerogel respectively;
[0131] The preparation process of the infrared shielding reflective layer is as follows: the infrared shielding material is attached to the substrate by glue, and the surface of the infrared shielding material is etched by a laser marking machine at a laser etching speed of 180 mm / s and an etching power of 90%, thereby obtaining an infrared shielding reflective layer having a laser-etched periodic pattern; the periodic unit shape of the periodic pattern is circular (SEM as shown in FIG. Figure 3 As shown in (d), the periodic unit size is 0.5 mm and the laser etching gap is 40 μm;
[0132] The preparation process of aerogel is as follows: the homogeneous dispersion of aramid nanofibers, MXene and Fe3O4@CPPy are mixed evenly, put into a mold, frozen in liquid nitrogen at -80°C for 12 hours, and then dried at -50°C to remove the solvent to obtain aerogel; the thickness of the aerogel is 2.7mm; the content of MXene in the aerogel is 25wt%, and the content of Fe3O4@CPPy is 30wt%;
[0133] (4) Preparation of radar-infrared multi-spectrum compatible stealth composite materials;
[0134] The infrared shielding reflective layer and the aerogel are assembled with glue to obtain a radar-infrared multi-spectrum compatible stealth composite material.
[0135] The radar-infrared multi-spectrum compatible stealth composite material finally prepared is composed of an upper infrared shielding reflection layer and a lower aerogel layer, and the infrared shielding reflection layer is composed of an upper infrared shielding material and a lower substrate;
[0136] The radar-infrared multi-spectrum compatible stealth composite material has an absorption bandwidth of 10.2-12.4 GHz in the X-band, and a minimum reflection loss of -36.1 dB; the maximum transmittance of the infrared shielding reflective layer to radar waves is 96.74%, and the minimum is 93.06%; the thermal conductivity of the radar-infrared multi-spectrum compatible stealth composite material is 0.0318 W / (m·K); the average infrared emissivity of the radar-infrared multi-spectrum compatible stealth composite material in the 3-5μm infrared band is 0.22, and the average infrared emissivity in the 8-14μm infrared band is 0.19. The surface temperature is 52.3°C after continuous heating on a 150°C heating table for 0.5h.
[0137] Example 6
[0138] A method for preparing a radar-infrared multi-spectrum compatible stealth composite material, the specific steps are as follows:
[0139] (1) Preparation of raw materials;
[0140] FeCl3-6H2O: CAS number is 10025-77-1;
[0141] Polyethylene glycol: CAS number is 25322-68-3;
[0142] Anhydrous sodium acetate: CAS number is 127-09-3;
[0143] Ethylene glycol: CAS number is 107-21-1;
[0144] Pyrrole monomer: CAS number is 109-97-7;
[0145] L - Camphorsulfonic acid solution: concentration is 1 mol / L, the solvent is deionized water;
[0146] Ammonium persulfate solution: concentration is 1 mol / L, the solvent is deionized water;
[0147] Infrared shielding material: copper foil, thickness 0.03mm;
[0148] Substrate: polycarbonate sheet, manufactured by Dongguan Hongyan Plastic Co., Ltd., thickness 0.15mm;
[0149] A homogenous dispersion of aramid nanofibers;
[0150] MXene: The manufacturer is Jiangsu Xianfeng Nanomaterials Co., Ltd., and the flake diameter is 1-20 μm;
[0151] Glue: The manufacturer is Shenzhen Yishangxiang Electronic Materials Co., Ltd., brand name is YS1996;
[0152] (2) Preparation of Fe3O4@CPPy;
[0153] FeCl3-6H2O, polyethylene glycol, and anhydrous sodium acetate were dissolved in ethylene glycol and reacted at 220°C for 10 h. After washing the reactants to obtain Fe3O4 nanoparticles, Fe3O4 nanoparticles and pyrrole monomers were added to L - Ammonium persulfate solution was added dropwise to the camphorsulfonic acid solution, and the mixture was polymerized in an ice-water bath for 2 h. The precipitate was washed to obtain Fe3O4@CPPy with an average particle size of 385 nm. The mass ratio of FeCl3-6H2O, polyethylene glycol and anhydrous sodium acetate was 1.5:1:3.6, the mass ratio of ethylene glycol to the total mass of FeCl3-6H2O, polyethylene glycol and anhydrous sodium acetate was 8:1, and the Fe3O4 nanoparticles, pyrrole monomers, and L - The mass ratio of camphorsulfonic acid solution to ammonium persulfate solution is 2:1.2:400:250;
[0154] (3) preparing an infrared shielding reflective layer and an aerogel respectively;
[0155] The preparation process of the infrared shielding reflective layer is as follows: the infrared shielding material is attached to the substrate by glue, and the surface of the aluminum foil is etched by a laser marking machine at a laser etching speed of 180 mm / s and an etching power of 90%, so as to obtain an infrared shielding reflective layer with a laser-etched periodic pattern; the periodic unit shape of the periodic pattern is a cross rectangle, which is composed of a rectangle and four line segments located inside it, one end of the four line segments is connected to the center point of the rectangle at the same time, and the other end is connected to the four vertices of the rectangle respectively, the periodic unit size is 0.7 mm, and the laser etching gap is 55 μm;
[0156] The preparation process of aerogel is as follows: the homogeneous dispersion of aramid nanofibers, MXene and Fe3O4@CPPy are mixed evenly, put into a mold, frozen in liquid nitrogen at -80°C for 12 hours, and then dried at -50°C to remove the solvent to obtain aerogel; the thickness of the aerogel is 2.5mm; the content of MXene in the aerogel is 20wt%, and the content of Fe3O4@CPPy is 30wt%;
[0157] (4) Preparation of radar-infrared multi-spectrum compatible stealth composite materials;
[0158] The infrared shielding reflective layer and the aerogel are assembled with glue to obtain a radar-infrared multi-spectrum compatible stealth composite material.
[0159] The radar-infrared multi-spectrum compatible stealth composite material finally prepared is composed of an upper infrared shielding reflection layer and a lower aerogel layer, and the infrared shielding reflection layer is composed of an upper infrared shielding material and a lower substrate;
[0160] The radar-infrared multi-spectrum compatible stealth composite material has an absorption bandwidth of 11.2-12.4 GHz in the X-band, and a minimum reflection loss of -17.3 dB; the maximum transmittance of the infrared shielding reflective layer to radar waves is 98.08%, and the minimum is 95.90%; the thermal conductivity of the radar-infrared multi-spectrum compatible stealth composite material is 0.320 W / (m·K); the average infrared emissivity of the radar-infrared multi-spectrum compatible stealth composite material in the 3-5 μm infrared band is 0.28, and the average infrared emissivity in the 8-14 μm infrared band is 0.26. The surface temperature is 58.6 °C after continuous heating on a 150 °C heating table for 0.5 h.
[0161] Example 7
[0162] A method for preparing a radar-infrared multi-spectrum compatible stealth composite material, the specific steps are as follows:
[0163] (1) Preparation of raw materials;
[0164] FeCl3-6H2O: CAS number is 10025-77-1;
[0165] Polyethylene glycol: CAS number is 25322-68-3;
[0166] Anhydrous sodium acetate: CAS number is 127-09-3;
[0167] Ethylene glycol: CAS number is 107-21-1;
[0168] Pyrrole monomer: CAS number is 109-97-7;
[0169] L - Camphorsulfonic acid solution: concentration is 0.5 mol / L, the solvent is deionized water;
[0170] Ammonium persulfate solution: concentration is 0.5 mol / L, the solvent is deionized water;
[0171] Infrared shielding material: conductive spray paint, the manufacturer is Shenzhen Jingzhe Technology Co., Ltd., the brand is Hailin Star, the thickness is 0.03mm;
[0172] Substrate: polycarbonate sheet, manufactured by Dongguan Hongyan Plastic Co., Ltd., thickness 0.15mm;
[0173] A homogenous dispersion of aramid nanofibers;
[0174] MXene: The manufacturer is Jiangsu Xianfeng Nanomaterials Co., Ltd., and the flake diameter is 1-20 μm;
[0175] Glue: The manufacturer is Shenzhen Yishangxiang Electronic Materials Co., Ltd., brand name is YS1996;
[0176] (2) Preparation of Fe3O4@CPPy;
[0177] FeCl3-6H2O, polyethylene glycol, and anhydrous sodium acetate were dissolved in ethylene glycol and reacted at 180°C for 8.5 h. After washing the reactants to obtain Fe3O4 nanoparticles, Fe3O4 nanoparticles and pyrrole monomers were added to L - Ammonium persulfate solution was added dropwise to the camphorsulfonic acid solution, and the mixture was polymerized in an ice-water bath for 3 h. The precipitate was washed to obtain Fe3O4@CPPy with an average particle size of 365 nm. The mass ratio of FeCl3-6H2O, polyethylene glycol and anhydrous sodium acetate was 1.2:1:3.6, the mass ratio of ethylene glycol to the total mass of FeCl3-6H2O, polyethylene glycol and anhydrous sodium acetate was 10:1, and the Fe3O4 nanoparticles, pyrrole monomers, and L - The mass ratio of camphorsulfonic acid solution to ammonium persulfate solution is 2:1:400:200;
[0178] (3) preparing an infrared shielding reflective layer and an aerogel respectively;
[0179] The preparation process of the infrared shielding reflective layer is as follows: the infrared shielding material is attached to the substrate by glue, and the surface of the aluminum foil is etched by a laser marking machine at a laser etching speed of 200 mm / s and an etching power of 80%, so as to obtain an infrared shielding reflective layer with a laser-etched periodic pattern; the periodic unit shape of the periodic pattern is a cross square, which is composed of a square and four line segments located inside it, one end of the four line segments is connected to the center point of the square at the same time, and the other end is connected to the four vertices of the square respectively, the periodic unit size is 0.80 mm, and the laser etching gap is 60 μm;
[0180] The preparation process of aerogel is as follows: the homogeneous dispersion of aramid nanofibers, MXene and Fe3O4@CPPy are mixed evenly, put into a mold, frozen in liquid nitrogen at -80°C for 12 hours, and then dried at -50°C to remove the solvent to obtain aerogel; the thickness of the aerogel is 3.5mm; the content of MXene in the aerogel is 25wt%, and the content of Fe3O4@CPPy is 15wt%;
[0181] (4) Preparation of radar-infrared multi-spectrum compatible stealth composite materials;
[0182] The infrared shielding reflective layer and the aerogel are assembled with glue to obtain a radar-infrared multi-spectrum compatible stealth composite material.
[0183] The radar-infrared multi-spectrum compatible stealth composite material finally prepared is composed of an upper infrared shielding reflection layer and a lower aerogel layer, and the infrared shielding reflection layer is composed of an upper infrared shielding material and a lower substrate;
[0184] The radar-infrared multi-spectrum compatible stealth composite material has an absorption bandwidth of 11.0-12.4 GHz in the X-band, and a minimum reflection loss of -17.6 dB; the maximum transmittance of the infrared shielding reflective layer to radar waves is 95.70%, and the minimum is 90.91%; the thermal conductivity of the radar-infrared multi-spectrum compatible stealth composite material is 0.0281 W / (m·K); the average infrared emissivity of the radar-infrared multi-spectrum compatible stealth composite material in the 3-5μm infrared band is 0.27, and the average infrared emissivity in the 8-14μm infrared band is 0.24. The surface temperature is 48.2°C after continuous heating on a 150°C heating table for 0.5h.
[0185] Example 8
[0186] A method for preparing a radar-infrared multi-spectrum compatible stealth composite material, the specific steps are as follows:
[0187] (1) Preparation of raw materials;
[0188] FeCl3-6H2O: CAS number is 10025-77-1;
[0189] Polyethylene glycol: CAS number is 25322-68-3;
[0190] Anhydrous sodium acetate: CAS number is 127-09-3;
[0191] Ethylene glycol: CAS number is 107-21-1;
[0192] Pyrrole monomer: CAS number is 109-97-7;
[0193] L - Camphorsulfonic acid solution: concentration is 1.2 mol / L, the solvent is deionized water;
[0194] Ammonium persulfate solution: concentration is 1.0 mol / L, the solvent is deionized water;
[0195] Infrared shielding material: aluminum foil, thickness 0.04mm;
[0196] Substrate: polycarbonate sheet, manufactured by Dongguan Hongyan Plastic Co., Ltd., thickness 0.15mm;
[0197] A homogenous dispersion of aramid nanofibers;
[0198] MXene: The manufacturer is Jiangsu Xianfeng Nanomaterials Co., Ltd., and the flake diameter is 1-20 μm;
[0199] Glue: The manufacturer is Shenzhen Yishangxiang Electronic Materials Co., Ltd., brand name is YS1996;
[0200] (2) Preparation of Fe3O4@CPPy;
[0201] FeCl3-6H2O, polyethylene glycol, and anhydrous sodium acetate were dissolved in ethylene glycol and reacted at 220°C for 10 h. After washing the reactants to obtain Fe3O4 nanoparticles, Fe3O4 nanoparticles and pyrrole monomers were added to L - Ammonium persulfate solution was added dropwise to the camphorsulfonic acid solution, and the mixture was polymerized in an ice-water bath for 3 h. The precipitate was washed to obtain Fe3O4@CPPy with an average particle size of 390 nm. The mass ratio of FeCl3-6H2O, polyethylene glycol and anhydrous sodium acetate was 1.3:1:3.4, the mass ratio of ethylene glycol to the total mass of FeCl3-6H2O, polyethylene glycol and anhydrous sodium acetate was 10:1, and the Fe3O4 nanoparticles, pyrrole monomers, and L - The mass ratio of camphorsulfonic acid solution to ammonium persulfate solution is 2:1.5:500:200;
[0202] (3) preparing an infrared shielding reflective layer and an aerogel respectively;
[0203] The preparation process of the infrared shielding reflective layer is as follows: the infrared shielding material is attached to the substrate by glue, and the surface of the aluminum foil is etched by a laser marking machine at a laser etching speed of 160 mm / s and an etching power of 85%, so as to obtain an infrared shielding reflective layer with a laser-etched periodic pattern; the periodic unit shape of the periodic pattern is a bagua shape, the periodic unit size is 1.0 mm, and the laser etching gap is 55 μm;
[0204] The preparation process of aerogel is as follows: the homogeneous dispersion of aramid nanofibers, MXene and Fe3O4@CPPy are mixed evenly, put into a mold, frozen in liquid nitrogen at -80°C for 12 hours, and then dried at -50°C to remove the solvent to obtain aerogel; the thickness of the aerogel is 2.5mm; the content of MXene in the aerogel is 20wt%, and the content of Fe3O4@CPPy is 25wt%;
[0205] (4) Preparation of radar-infrared multi-spectrum compatible stealth composite materials;
[0206] The infrared shielding reflective layer and the aerogel are assembled with glue to obtain a radar-infrared multi-spectrum compatible stealth composite material.
[0207] The radar-infrared multi-spectrum compatible stealth composite material finally prepared is composed of an upper infrared shielding reflection layer and a lower aerogel layer, and the infrared shielding reflection layer is composed of an upper infrared shielding material and a lower substrate;
[0208] The radar-infrared multi-spectrum compatible stealth composite material has an absorption bandwidth of 8.6-11.7 GHz in the X-band, and a minimum reflection loss of -21.6 dB; the maximum transmittance of the infrared shielding reflective layer to radar waves is 96.29%, and the minimum is 92.11%; the thermal conductivity of the radar-infrared multi-spectrum compatible stealth composite material is 0.0310 W / (m·K); the average infrared emissivity of the radar-infrared multi-spectrum compatible stealth composite material in the 3-5μm infrared band is 0.28, and the average infrared emissivity in the 8-14μm infrared band is 0.26. The surface temperature is 58.6°C after continuous heating on a 150°C heating table for 0.5h.
Claims
1. A radar-infrared multi-spectrum compatible stealth composite material having a double-layer structure, wherein the upper layer is an infrared shielding reflection layer having a laser-etched periodic pattern, and the lower layer is a wave-absorbing and heat-insulating layer, characterized in that: The periodic unit of the periodic pattern is in the shape of a cross rectangle, a diamond, a bagua, a cross circle, a circle or a cross rectangle; The cross-shaped rectangle is composed of a rectangle and eight line segments inside it. One end of the eight line segments is connected to the center point of the rectangle at the same time, and the other ends are connected to the four vertices of the rectangle and the midpoints of the four sides of the rectangle respectively. The cross circle is composed of a circle and four line segments inside it. One end of the four line segments is connected to the center of the circle at the same time, and the other end is connected to four points evenly distributed on the circle. The cross rectangle consists of a rectangle and four line segments inside it. One end of the four line segments is connected to the center point of the rectangle at the same time, and the other end is connected to the four vertices of the rectangle respectively. The periodic unit size is 0.5-1.0 mm, and the laser etching gap is 35-60 μm.
2. The radar-infrared multi-spectrum compatible stealth composite material according to claim 1, characterized in that: The infrared shielding reflective layer includes an infrared shielding material located at the upper layer and a substrate located at the lower layer. The thickness of the infrared shielding material is 0.03-0.1mm, and the thickness of the substrate is 0.1-0.2mm. The infrared shielding material is aluminum foil, copper foil, silver foil, indium tin oxide film or conductive spray paint, and the substrate is a polycarbonate board.
3. The radar-infrared multi-spectrum compatible stealth composite material according to claim 1, characterized in that: The thickness of the wave-absorbing and heat-insulating layer is 2.5-3.5 mm; the wave-absorbing and heat-insulating layer is aerogel, the skeleton of the aerogel is aramid nanofiber, and the aramid nanofiber is obtained by sequentially deprotonating and protonating short-cut Kevlar fibers in a solvent.
4. The radar-infrared multi-spectrum compatible stealth composite material according to claim 3, characterized in that: MXene is attached to the aramid nanofibers, and the diameter of the MXene sheets is 1-20μm.
5. The radar-infrared multi-spectrum compatible stealth composite material according to claim 4, characterized in that: Fe3O4@CPPy is also attached to the aramid nanofibers. Fe3O4@CPPy is a chiral nanoparticle with a core-shell structure, in which the core is Fe3O4 nanoparticles and the shell is chiral polypyrrole, with an average particle size of 340-400nm.
6. The radar-infrared multi-spectrum compatible stealth composite material according to claim 5, characterized in that: The preparation process of Fe3O4@CPPy is as follows: after Fe3O4 nanoparticles are prepared by a hydrothermal method, they are added together with pyrrole monomers into a system containing a chiral dopant or a chiral acid for polymerization to obtain Fe3O4@CPPy.
7. The radar-infrared multi-spectrum compatible stealth composite material according to claim 6, characterized in that: The preparation process of Fe3O4@CPPy is as follows: FeCl3-6H2O, polyethylene glycol, and anhydrous sodium acetate are dissolved in ethylene glycol, reacted at 180-220°C for 8-10h, the reactant is washed to obtain Fe3O4 nanoparticles, and then the Fe3O4 nanoparticles and pyrrole monomer are added to L-Hydroxypropene with a concentration of 0.5-1.5 mol / L. - Ammonium persulfate solution was added dropwise to the camphorsulfonic acid solution, polymerized in an ice-water bath for 2-4 h, and the precipitate was washed to obtain Fe3O4@CPPy.
8. The radar-infrared multi-spectrum compatible stealth composite material according to claim 5, characterized in that: In the aerogel, the content of MXene is 20-30wt%, and the content of Fe3O4@CPPy is 10-30wt%.
9. The radar-infrared multi-spectrum compatible stealth composite material according to any one of claims 1 to 8, characterized in that: The radar-infrared multi-spectrum compatible stealth composite material has an absorption bandwidth of 8.4-12.4GHz in the X-band, a minimum reflection loss of -32.44~-14.4dB, a thermal conductivity of 0.0274-0.0320W / (mK), an average infrared emissivity of 0.18-0.28 in the 3-5μm infrared band, and an average infrared emissivity of 0.15-0.26 in the 8-14μm infrared band. After continuous heating on a 150℃ heating table for 0.5h, the surface temperature is 46.6-58.6℃.
10. A method for preparing a radar-infrared multi-spectrum compatible stealth composite material as claimed in any one of claims 1 to 9, characterized in that: After separately preparing an infrared shielding reflection layer and a wave-absorbing heat-insulating layer with a laser-etched periodic pattern, the two are assembled together by glue to obtain a radar-infrared multi-spectrum compatible stealth composite material.
Citation Information
Patent Citations
Radar and infrared compatible stealthy material and preparation method thereof
CN102179968A
Wave-absorbing printing paste, flexible light composite wave-absorbing fabric and preparation method and application of flexible light composite wave-absorbing fabric
CN116497615A
High-strength composite film with conductivity and electromagnetic shielding performance and preparation method and application thereof
CN117529073A
Adjustable radar wave-absorbing metamaterial and preparation method and application thereof
CN118281581A
Electromagnetic wave shieldable adhesive film, electromagnetic wave shielding constitution using the film and display
JP2003015533A
Cited By
Multiband compatible stealth and camouflage integrated material and preparation method thereof
CN121994079A